Quels critères pour quelles démarches d’investigation ? Articuler esprit créatif et esprit de contrôle - Jean-Yves Cariou (Recherches en Éducation)
The international promotion of inquiry-based learning and the approaches under this common banner in France, in experimental science, technology and mathematics, question the very meaning of the term, as well as its unity and diversity. Any activity performed by learners seems to qualify for an inquiry, simply because the students are active or actors. However, the promotion of inquiry has a deeper meaning, which transpires in its origins: epistemological, psychological and educational considerations have historically contributed to advocate an approach in which the essential elements of the research spirit could be implemented in the classroom. Attempts to define and characterize inquiry have been made, but not always with an emphasis on those fundamental principles. Referring to the considerations emanating from those various fields allows to bring these principles back to foreground, to pay attention to their being mentioned in speeches about inquiry, and to consider the criteria along which they may be implemented in natural sciences, mathematics and technology classes.